Bridging Numeracy and Critical Reasoning through Realistic Mathematics Education: Evidence from a Mixed-Methods Classroom Intervention - Rustam Effendy Simamora; Heldina L. Toruan (Journal of Honai Math, 2025)
Critical thinking in numeracy contexts (CTNC) is a core twenty-first-century competency, yet its systematic development remains limited in conventional mathematics instruction. Realistic Mathematics Education (RME) offers a theoretically grounded approach to fostering CTNC through contextualised problem solving, guided reinvention, and collaborative discourse. This mixed-methods study investigated the effectiveness of RME in enhancing CTNC among junior secondary students and examined their experiential learning processes. Thirty-eight Year 7 students (n = 19 per class) were selected via cluster sampling. A quasi-experimental, non-randomised control group design with pre-test and post-test measures was employed in the quantitative phase. The qualitative phase involved three waves of semi-structured interviews with six purposively selected students, using member checking and theoretical sampling until data saturation was achieved. Results indicated a statistically significant improvement in CTNC for students in the RME group compared to those receiving conventional instruction, t(36) = 5.55, p < .001. Thematic analysis revealed three interconnected dimensions: enhanced contextual sense-making through engagement with realistic tasks; deepened critical reasoning facilitated by structured peer discourse; and increased metacognitive awareness during strategy evaluation. Students also reported greater engagement and perceived relevance of mathematics to everyday contexts. These findings suggest that RME effectively strengthens CTNC by linking abstract numeracy to authentic experiences through collaborative inquiry. The study highlights the importance of systematically integrating context-rich, discussion-oriented pedagogies into secondary mathematics curricula.